2014
DOI: 10.1111/cas.12349
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐proliferative and apoptosis‐inducing activity of lycopene against three subtypes of human breast cancer cell lines

Abstract: Although lycopene, a major carotenoid component of tomatoes, has been suggested to attenuate the risk of breast cancer, the underlying preventive mechanism remains to be determined. Moreover, it is not known whether there are any differences in lycopene activity among different subtypes of human breast cancer cells. Using ER/PR positive MCF-7, HER2-positive SK-BR-3 and triple-negative MDA-MB-468 cell lines, we investigated the cellular and molecular mechanism of the anticancer activity of lycopene. Lycopene tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(54 citation statements)
references
References 39 publications
4
48
0
2
Order By: Relevance
“…Flow cytometry assay showed that lycopene induced the apoptosis of MCF-7 cells in a dose-and time-dependent manner, indicating that lycopene inhibited cell proliferation by inducing MCF-7 cell apoptosis. The results of our study were consistent with those of previous studies, which showed that lycopene can arrest cells at G0/G1 phase to inhibit MCF-7 cell proliferation (Takeshima et al, 2014) and induce apoptosis (Teodoro et al, 2012), and provided further evidences on the anti-tumor effects of lycopene on ER (+) breast cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Flow cytometry assay showed that lycopene induced the apoptosis of MCF-7 cells in a dose-and time-dependent manner, indicating that lycopene inhibited cell proliferation by inducing MCF-7 cell apoptosis. The results of our study were consistent with those of previous studies, which showed that lycopene can arrest cells at G0/G1 phase to inhibit MCF-7 cell proliferation (Takeshima et al, 2014) and induce apoptosis (Teodoro et al, 2012), and provided further evidences on the anti-tumor effects of lycopene on ER (+) breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Bax is also a downstream effector of early p53 response gene (Brady and Gil-Gómez, 1998). A previous study showed cell cycle arrest by lycopene (Takeshima et al, 2014). Given the contradicting results obtained from previous studies, the exact role of lycopene in MCF-7 cells, which is an ER (+) breast cancer cell line, remains poorly understood.…”
Section: Introductionmentioning
confidence: 93%
“…Lycopene, as a chemopreventive candidate for a variety of cancers, has been increasingly reported to induce prolonged anticancer effects. The anti-tumor capacity of lycopene has been found in wide range of cancer cells of different organs and induced carcinogenesis in animal models, including breast cancer cells [Takeshima et al, 2014], prostate cancer cells [Assar et al, 2016;Graff et al, 2016], Renal cell carcinoma [Sahin et al, 2015], hepatocarcinogenesis [Sahin et al, 2014], etc. whether it has anti-cancer effects on skin cancer during UVB exposure, especially the molecular mechanisms underlying those effects are yet not clearly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Lycopene is a 40-carbon aliphatic chain containing thirteen trans-double bonds, eleven of which are conjugated [72]. Lycopene treatment for seven consecutive days induced strong and sustained activation of the ERK1/2 with downstream cyclin D1 suppression and p21 upregulation [74].…”
Section: Anti-cancer Effects Of Phytochemicals Using Mcf-7 Cell Linementioning
confidence: 99%